Maternal Anaemia and Low Birth Weight in Gowa District, Indonesia - Burhan, Siti Latifah; Bujawati, Emmi; Syarfaini, Syarfaini; Adha, Andi Syamsiah (Diversity: Disease Preventive of Research Integrity, 2022)
Low Birth Weight (LBW) is the main cause of the high infant mortality rate, especially in the perinatal period. LBW is extremely susceptible to infection, a very big risk of experiencing problems when the baby grows up to adulthood. This study aimed to determine the association between high-risk expectant mother (mother's age, gestational age, maternal anemia, maternal nutritional status, and family socioeconomic status) with LBW. This research was a quantitative research with an observational analytic approach with a case control study design. The population in this study were all mothers who gave birth to babies in the working area of Somba Opu Health Center in 2020-2021. The sample in this study were 64 expectant mothers consisting of 32 cases and 32 controls taken by using a purposive sampling technique with the inclusion criteria of expectant mothers domiciled in Somba Opu sub-district having completed examination records. The association analysis used Chi Square test with 95% confidence interval. The results showed that there was a significant association between maternal anemia with LBW (p=0,003, OR=7) and there is no association between maternal age (p=0,305, OR=1,9), gestational distance (p=0,426, OR=2,8), maternal nutritional status (p=0,197, OR=2,3), and socioeconomic status of the family (p=0,238, OR=2,5) with LBW in the working area of Somba Opu Health Center, Gowa Regency in 2021. The researcher recommends that the expectant mothers routinely perform ANC in order to increase early detection of high-risk expectant mothers, and increase maternal nutritional intake by consuming balanced nutrition, taking Fe tablets, doing PMT for expectant mothers which can increase maternal Hb levels.